In vitro and ex vivo antitubercular activity of diarylheptanoids from the rhizomes of alpinia officinarum hance - Honmore, Varsha S.; Rojatkar, Supada R.; Nawale, Laxman U.; Arkile, Manisha A.; Khedkar, Vijay M.; Natu, Arun D.; Sarkar, Dhiman (Natural Product Research, 2016)
Phytochemical investigation of methanol extract of the rhizomes of Alpinia officinarum Hance afforded four known diarylheptanoids 1,7-diphenylhept-4-en-3-one (1), 5-hydroxy-1,7-diphenyl-3-heptanone (2), 5-hydroxy-7-(4 ''-hydroxy-3 ''-methoxyphenyl)-1-phenyl-3-heptanone (3), and 7-(4 ''-hydroxy-3 ''-methoxyphenyl)-1-phenyl heptan-3-one (4).The acetate derivative of (4), 7-(4 ''-actetate-3 ''-methoxy phenyl)-1-phenyl heptan-3-one (5), was prepared. These diarylheptanoids exhibited promising in vitro and ex vivo antitubercular activity for the first time against dormant Mycobacterium tuberculosis H37Ra with the IC50 values between 0.3447.69 and 0.1322.91 mu M, respectively. All compounds showed comparable activity against Mycobacterium bovis BCG (dormant phage) and did not show any activity against two gram + ve and two gram -ve bacterial strains. These compounds were also weakly cytotoxic up to 300 mu M against three human cancer cell lines THP-1, Panc-1 and A549.

Isolates of alpinia officinarum hance as COX-2 inhibitors: evidence from anti-inflammatory, antioxidant and molecular docking studies - Honmore, Varsha S.; Kandhare, Amit D.; Kadam, Parag P.; Khedkar, Vijay M.; Sarkar, Dhiman; Bodhankar, Subhash L.; Zanwar, Anand A.; Rojatkar, Supada R.; Natu, Arun D. (International Immunopharmacology, 2016)
Background: Inflammation triggered by oxidative stress can cause various ailments, such as cancer, rheumatoid arthritis, asthma, diabetes etc. In the last few years, there has been a renewed interest in studying the antioxidant and anti-inflammatory action of plant constituents such as flavonoids and diarylheptanoids. Aim: To evaluate the antioxidant, anti-inflammatory activity and the total phenolic content of isolated compounds from Alpinia officinarum rhizomes. Furthermore, molecular docking was performed to study the binding mode of these compounds into the active site of cyclooxygenase-2 (COX -2). Methods: A. officinarum rhizomes were extracted by maceration, using methanol. This extract was further fractionated by partitioning with hexane, chloroform and ethyl acetate and these fractions on further purification resulted in isolation of five pure compounds. Characterization was carried out by using H-1 NMR, C-13 NMR and MS. They were further evaluated for antioxidant and anti-inflammatory activity using carrageenan-induced paw edema model in rats. Molecular docking study was performed using Glide module integrated in Schrodinger molecular modeling software. Results: The compounds were identified as 1,7-diphenylhept-4-en-3-one (1), 5-hydroxy-1,7-diphenyl-3-heptanone (2), 3,5,7-trihydroxyflavone (Galangin, 3), 3,5,7-trihydroxy-4'-methoxyflavone (Kaempferide, 4) and 5-hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone (5). The compound-3 and compound-5 (10 mg/kg) showed significant (p < 0.001) antioxidant and anti-inflammatory potential. Moreover, total phenolic content was detected as 72.96 mg and 51.18 mg gallic acid equivalent respectively. All the five isolates were found to be good binders with COX-2 (average docking score -9.03). Conclusions: Galangin and 5-hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone exhibited anti-inflammatory and in-vitro antioxidant activity which may be due to presence of phenolic content in it. The molecular docking study revealed that these compounds have affinity towards COX-2 active site which can further be explored as selective COX-2 inhibitors. The results obtained in this work justify the use of A. officinarum in the treatment of inflammatory disorders like rheumatoid arthritis and inflammatory bowel diseases. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: 5-Hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone; Alpinia officinarum; Anti-inflammatory; Antioxidant; COX-2 inhibitors; Galangin